Pengaruh Perceived Value terhadap Repurchase Intention Melalui E-Word of Mouth Online Shopping Tokopedia di Kota Bandung - Magali, Shara Syifa; Evangalista, Leni (Universitas Batanghari, 2024)
The purpose of this study was to examine the effect of perceived value on repurchase intention mediated by e-word of mouth online shopping Tokopedia in Bandung City. This study involved 90 respondents who had shopped online at Tokopedia. Data was collected by distributing online questionnaires and the time horizon used was one shot study or cross sectional. The data analysis technique uses simple linear regression, multiple linear regression using SPSS version 25 software, and the sobel test. Of the four research hypotheses proposed, three of them are supported by empirical data. The research findings show that perceived value has a positive impact on repurchase intention. Furthermore, e-WOM mediates the effect of perceived value on repurchase intention. Future research can propose new concepts that are thought to have a positive effect on repurchase intention. The results of this study are expected to provide benefits for future research and the managers of the object being assessed or similar e-commerce regarding the design of developing strategies that are in accordance with improving the quality of these attributes.